Family Business Management in Small and Medium Enterprises at Nellore District - M. Chandraiah, C. Prakash, R. Vani, (International Journal of Scientific Research and Management (IJSRM), 2016)
Family businesses constitute most businesses in India. Economic liberalization and rapid expansion in the industrial base inrecent years have not only created growth opportunities for many but also have tested their resource capabilities to respond tothem. Family business management stands for “A family business is a company owned, controlled, and operated by membersof one or several families. Many companies that are now publicly held were founded as family businesses. Many familybusinesses have non-family members as employees, but, particularly in smaller companies, the top positions may be allocatedto family members” Family Business contributes 60-70 percent of GDP of most developed & developing countries. Numberof challenges face by Indian family businesses today. My study covers key determinant factors which influence the familybusiness, leadership style, role of women, initial problems of entrepreneurs in family business and family businessmanagement in India.